Eco-innovation diversity in a circular economy: Towards circular innovation studies - Jesus, A. de (2021)
Transition to a Circular Economy (CE) is about structural change and is predicated on the introduction of transformative eco-innovation (EI). Research on the CE–EI nexus has recently attracted attention both from an analytical and regulatory perspective. However, in-depth research exploring EI dynamics within the CE is still marginal, especially concerning the trends and dynamics of the pro-CE innovation policy and strategy. This paper addresses this gap by taking advantage of the burgeoning research on CE of the last 20 years and offers a new working synthesis. By implementing a “(systematic) review of (systematic) reviews”, this paper provides a new comprehensive framework for understanding pro-circular innovation strategies and, as a complement, argues the need to advance “circular innovation studies” as an agenda in its own right. Innovations related to recycling and recovery CE strategies along with business-model innovations and systemic/transformative innovations are found to be a major current trend in the research, connecting supply and demand side innovations and also driving other forms of innovation linked to design, product manufacturing, logistics and reverse logistics and end-of-life management and recovery. Additionally, of note is that the conceptual understanding of EI dynamics within a CE is still mainly implicit (rather than explicitly discussed) limiting the possibilities to advance knowledge in the area of innovation for CE: this is why we propose a “circular innovation studies” agenda.